A Customized Tool of Incident Reporting for the Detection of Nonconformances at a Single IVF Center: Development, Application, and Efficacy. (21st October 2021) - Morini, Daria; Daolio, Jessica; Nicoli, Alessia; De Feo, Gaetano; Valli, Barbara; Melli, Beatrice; Sibahi, Arua; Tranquillo, Maria Lucrezia; Mezzadri, Cecilia; Ragni, Pietro; Aguzzoli, Lorenzo; Villani, Maria Teresa
Abstract : In IVF centers, risk assessment applies to complex processes potentially accounting for adverse events and reactions that undergo well-established legislative oversight, and nonconformances (NCs), that lack of established tracking systems. NCs account for an integral part of the quality management system, so that their documentation is important. The study evaluated the performance of a customized tool for incident reporting (IR) to track and characterize NCs in a public IVF center. IVF operators used the IVF-customized IR tool to record NCs at the moment of detection or subsequently, and in a time-saving manner during daily practice. From February 2015 to February 2020, 635 NCs were reported leading to the implementation of 10 operative instructions and 3 procedures with corrective strategies. NCs referred to the IVF laboratory were the most numerically meaningful (454/635, 71.5%). The majority (352/454, 77.5%) accounted for NCs related to procedures of sample management; considering the analytical phase as all the procedures involving sample treatment, the intra-analytical phase (176/352, 50%) has always been more subject to NCs compared to pre- (102/352, 29%) and postanalytical (74/352, 21%) phases. Our experience showed that the IVF-customized IR tool is suitable for application in IVF with regard to NC reports and documentation, as it identifies the most vulnerable steps of treatments. It manages NCs over the time, but it requires a contextual understanding of its application in order to avoid NC underestimates that could negatively influence the safety and quality aspects of IVF treatments.